Improving Senior High School EFL Students’ Argumentative Speech Performance Through Mnemonic Cues: A Quasi-Experimental Study - Aljalis, Anis; Susanto, Dias Andris; Setyaji, Arso (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Speaking is a crucial component of English as a Foreign Language (EFL) learning; however, many Indonesian senior high school EFL students struggle to deliver well-structured argumentative speeches due to difficulties in recalling ideas and organizing arguments during real-time speech production. These challenges often result in hesitation, limited fluency, and weak argument development. To address this problem, this study investigates whether mnemonic cues can improve students’ argumentative speech performance. This study employed a quantitative quasi-experimental design using non-equivalent control group. The research involved 68 Indonesian senior high school EFL students divided into an experimental group taught with mnemonic cue-based instruction and a control group taught with conventional instruction. Data were collected through an argumentative speech performance test and analyzed using descriptive statistics, paired samples t-tests, independent samples t-tests, and effect size analysis. The findings revealed a statistically significant improvement in the experimental group (p<0.05), with the mean score increasing from 51.29 to 78.00 (mean gain=26.71). The effect size analysis yielded a Cohen’s d value of 1.47, indicating a very large effect. These results suggest that mnemonic cues function as effective cognitive scaffolding tools that support students in organizing arguments and maintaining fluency during speech delivery. The study provided empirical support for integrating mnemonic cues into EFL speaking instruction. It is recommended that teachers incorporate mnemonic cues as structured support to improve argumentative speech performance among Indonesian senior high school EFL students.